Pengaruh Pengalaman Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Beban Kerja Sebagai Variabel Intervening - Hidayat, Syahrijal; Irwadi, Irwadi; Wahyuni, Neni Sri (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to analyze the influence of work experience, job satisfaction and workload on employee performance. This research uses descriptive quantitative methods. The data analysis method used in this research is Multiple Linear Regression analysis, hypothesis testing and Path analysis with the help of SPSS version 25. The results of the research show that: 1) work experience, job satisfaction and employee performance are in the high category and workload is in the sufficient category tall. 2) Work experience has a significant negative effect on workload. 3) Job satisfaction has a significant negative effect on workload. 4) Work experience has a significant positive effect on employee performance. 5) Job satisfaction has a significant positive effect on employee performance. 6) Workload has a significant negative effect on employee performance. 7) Work experience has a positive effect on employee performance through workload. 8) Job satisfaction has a positive effect on employee performance through workload. This shows that the role of workload as a partial mediator is able to bridge the influence of work experience and job satisfaction, both directly and indirectly, on employee performance.